Management Strategies to Address Human Resources Challenges in the Information Technology Era - Rokhadi; Sukistanto; Hariyanti; Dede Mariyani (Politeknik Ganesha Medan, 2023)
The Information Technology era has brought significant changes in various aspects of human life, including the business world. In the midst of these changes, Human Resources become a key element in achieving success and competitive advantage. The purpose of this study is to examine management strategies to overcome human resources challenges in the era of information technology. This study involves a qualitative research methodology, specifically a literature review, in which data will be analysed and interpreted based on information and textual content gathered from diverse sources. The study results show that managing Human Resources in the era of rapid information technology is a complex challenge, but also key to an organisation's success and competitive advantage. In this context, some of the key challenges include rapid technological change, information security, and changes in ways of working and collaboration. To overcome these challenges, organisations need to develop appropriate management strategies.